Prevention of shaken baby syndrome: Never shake a baby - Ward, Michelle GK (Pulsus Group Inc, 2004)
Shaken baby syndrome (SBS) represents injuries to the head, skeleton and eyes of a young child and is the leading cause of fatal or life-threatening child abuse. SBS is preventable. The dangers and consequences of shaking a baby are not well appreciated by the general public. Simple educational programs and community nursing support programs have been shown to be helpful. Inadequate physician training and knowledge in child maltreatment have also been identified as problems. This article outlines the evidence for interventions in the prevention of SBS and recommendations for health care providers and educators.